2005
DOI: 10.1007/s00192-004-1263-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of leak point pressure methods in an animal model of stress urinary incontinence

Abstract: We compared three different methods of testing leak point pressure (LPP) in rats with or without the pudendal nerves and nerves to the iliococcygeus/pubococcygeus muscles transected: (1) sneeze induced with a whisker in the nostril (sneeze LPP), (2) manually increased abdominal pressure (Crede LPP), and (3) increased intravesical pressure using the vertical tilt table method (vertical tilt table LPP). In sham rats, passive intravesical pressure rises in Crede and vertical tilt table methods induced active uret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
72
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 68 publications
(77 citation statements)
references
References 30 publications
4
72
1
Order By: Relevance
“…Pelvic floor inhibition during voiding suggests similarities between rats and humans in the neural control of micturition. Some studies in rats have shown that levator ani denervation decreases urethral pressure and that neurectomized rats leak at sneeze (Conway et al 2005;Kamo et al 2003). However, we could not demonstrate a pelvic floor response during a LPP test and the LPP value did not decrease after levator ani nerve transection .…”
Section: Discussioncontrasting
confidence: 90%
“…Pelvic floor inhibition during voiding suggests similarities between rats and humans in the neural control of micturition. Some studies in rats have shown that levator ani denervation decreases urethral pressure and that neurectomized rats leak at sneeze (Conway et al 2005;Kamo et al 2003). However, we could not demonstrate a pelvic floor response during a LPP test and the LPP value did not decrease after levator ani nerve transection .…”
Section: Discussioncontrasting
confidence: 90%
“…Sievert et al (33) also found that immunoreactivity in proximal and middle urethral segments for neuronal nitric oxide synthase and tyrosine hydroxylase (marker for sympathetic nerves) significantly declined after VD was induced. Neurally mediated urethral closure mechanisms (via somatic nerves) have been proposed by Kamo et al (7,17) to mediate increases in urethral pressure before sneeze transmission, followed by an increase in urethral resistance as sneeze-induced abdominal pressure exceeds increased bladder pressure. The involvement of neural mechanisms in urethral resistance is also supported by the fact that, with bilateral pudendal nerve block, there is a significant decrease in urethral closure pressure (39).…”
Section: Discussionmentioning
confidence: 99%
“…Six rats of each sex were used to measure LPP via the vertical-tilt table method (11,29). The vertical-tilt table method was used in this study since it is more sensitive and reliable for measuring resting state LPP than is manual compression of the Crede method (11).…”
Section: General Preparations the Institutional Animal Care And Usementioning
confidence: 99%
“…Six rats of each sex were used to measure LPP via the vertical-tilt table method (11,29). The vertical-tilt table method was used in this study since it is more sensitive and reliable for measuring resting state LPP than is manual compression of the Crede method (11). Before the tests, the spinal cord was acutely transected at the T 9-T10 level to eliminate reflex bladder activity in response to increasing IVP, but this did not interfere with the spinal continence reflexes of the bladder neck or urethra (11,22,24).…”
Section: General Preparations the Institutional Animal Care And Usementioning
confidence: 99%
See 1 more Smart Citation